TASMI' BIL GHOIB ASSESSMENT MODEL OF THE QUR'AN FOR CHILDREN: CASE STUDY IN MULTICITY - S Suwardi; Sofyan Anif; W Waston; Yusuf Olawale Owa-Onire Uthman (Universitas Muhammadiyah Surakarta, 2023)
This study aims to describe the al-Qur'an Tahfiz Assessment Model and the effectiveness of its implementation. This case study research was conducted in three elementary schools that have a Holy Scripture memorization program. The data sources for this research were school principals, curricula deputy heads, tahfiz program coordinators, tahfiz teachers, students, and students' families. Data were collected by interview, observation, and documentation techniques and analyzed using a descriptive interpretative model proposed by Miles, Huberman, and Saldana, involving data collection, reduction, presentation, and conclusion. The results of the study show the following: (1) There are three models of memorization assessment used in all these schools, namely assessment based on type, period and achievement results. (2) There are 3 aspects of similarity in the assessment model applied, namely based on type, period and results. The difference is in the implementation where each has standards including a) aspects assessed; b) valuation techniques; c) assessment time; d) target assessment; and e) tone standards. (3) The assessment model is measured from the psychological effectiveness of the students, the spiritual of the students is effective, and the result of the most effective memorization is tasmi' bil ghoib because it is thorough and traceable. The conclusion that can be drawn from these findings is that the tasmi' bil ghoib assessment model is very effective for application in elementary schools because this method takes into account the psychological and spiritual factors of students so that the student's memorization results are fairly even and the memorization results are maximized.